2014
DOI: 10.1007/s13280-014-0521-z
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Spatial Variability Among CO2, CH4, and N2O Gas Fluxes from an Urban Forest Soil in Japan

Abstract: The spatial variability of carbon dioxide (CO 2 ), methane (CH 4 ), and nitrous oxide (N 2 O) fluxes from forest soil with high nitrogen (N) deposition was investigated at a rolling hill region in Japan. Gas fluxes were measured on July 25th and December 5th, 2008 at 100 points within a 100 9 100 m grid. Slope direction and position influenced soil characteristics and site-specific emissions were found. The CO 2 flux showed no topological difference in July, but was significantly lower in December for north-sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 27 publications
1
6
0
1
Order By: Relevance
“…Our results were consistent with a previous study that soil organic matter and nitrogen were higher in broadleaf forests than those under coniferous forests [34]. Similarly, several authors have already reported lower nutrient contents in coniferous stands in comparison with hardwoods stands [35][36]. The higher total C and total N in two broadleaf forests could likely be constant organic matter inputs, rhizodeposition, and the release and recycling of nutrients [37].…”
Section: Different Revegetation Types Contributing To Different Soil supporting
confidence: 92%
“…Our results were consistent with a previous study that soil organic matter and nitrogen were higher in broadleaf forests than those under coniferous forests [34]. Similarly, several authors have already reported lower nutrient contents in coniferous stands in comparison with hardwoods stands [35][36]. The higher total C and total N in two broadleaf forests could likely be constant organic matter inputs, rhizodeposition, and the release and recycling of nutrients [37].…”
Section: Different Revegetation Types Contributing To Different Soil supporting
confidence: 92%
“…Evaluation of the magnitude of N 2 O emissions requires a model of the N cycle, and the data needed for calibration and validation of such a model differ from those used to estimate CO 2 and methane (CH 4 ) emissions. Second, N 2 O emissions from soil, one of the major sources, are quite heterogeneous spatially and vary greatly temporally (e.g., Nishina et al 2012;Bellingrath-Kimura et al 2015). In soils, instantaneous N 2 O production occurs within microzones (i.e., hot spots) of high-microbial activity and bursts of N 2 O emissions often occur after rainfall and thawing of frozen soil (e.g., Kim et al 2012;Muhr et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the precise mechanism for the effect of N fertilizer application on soil respiration needs further investigation. Increased total N content led to a decreased C/N ratio and improved soil CO 2 flux (Bellingrath-Kimura et al, 2015;Pires et al, 2017). Furthermore, soil N/P ratio also influenced autotrophic respiration and microbial activity.…”
Section: Effects Of Fertilization Levelmentioning
confidence: 99%
“…Furthermore, soil N/P ratio also influenced autotrophic respiration and microbial activity. A balanced N/P ratio increased root biomass accumulation and soil CO 2 concentration (Bellingrath-Kimura et al, 2015;Pires et al, 2017;Sun et al, 2018). Nitrogen fertilizer application enhanced the root respiration rate by increasing the availability of soil nutrients, the N content in root, and photosynthate allocation below the ground (root biomass) (Sun et al, 2018).…”
Section: Effects Of Fertilization Levelmentioning
confidence: 99%